2018
DOI: 10.32604/jrm.2018.00015
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Synthesis of Inulin Acetate as Potential Bio-Based Additive for Poly(Vinyl Chloride)

Abstract: The paper presents the findings of an experimental study on the microwave synthesis (MW) of inulin acetate and its possible application as bio-additive in poly(vinyl chloride) (PVC). The obtained inulin acetate has been identified and characterized by spectroscopic methods. Advantages of the MW compared with the conventional synthesis were defined. In order to evaluate possible application of the product as bio-based additive for polymers, effect of the inulin ester on PVC behavior and characteristics has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The peak wave number of sucrose oleate in the C=O group was with K2CO3 catalyst and Na2CO3 catalyst which was 1,745.58 cm -1 . The dominant peak is in agreement with the research of [28], where the stretch on the C=O group of the ester was obtained from the transesterification of sucrose palmitate. In addition, the detection of bands in the range of 3,083 cm -1 (C=O) and 1,652 cm -1 indicated that there was a double bond in the vinyl group, so that the ester can be stable during the synthesis process.…”
Section: Ftir Analysis Of Sucrose Esterssupporting
confidence: 90%
“…The peak wave number of sucrose oleate in the C=O group was with K2CO3 catalyst and Na2CO3 catalyst which was 1,745.58 cm -1 . The dominant peak is in agreement with the research of [28], where the stretch on the C=O group of the ester was obtained from the transesterification of sucrose palmitate. In addition, the detection of bands in the range of 3,083 cm -1 (C=O) and 1,652 cm -1 indicated that there was a double bond in the vinyl group, so that the ester can be stable during the synthesis process.…”
Section: Ftir Analysis Of Sucrose Esterssupporting
confidence: 90%
“…P-MAM-g demonstrated an improved plasticization ability in comparison to PVC/40DOP and pure PVC. Grafting ester group, hexatomic ring and longer alkyl chains simultaneously onto PVC decreased the polymer-polymer interaction and enhanced the free volume between polymer molecules, which is helpful for decreasing the T g of P-MAM-g [26][27][28]. The above analysis verifies that the introduction of multifunctional mannich base derived from myrcene into PVC is an effective strategy for providing PVC with intrinsic plasticization abilities.…”
Section: Mechanical Propertiesmentioning
confidence: 55%
“…According to previous reports, plasticizers and thermal stabilizers are the main sources of organic by-products [13,14]. The thermal stabilizer, plasticizer and PVC are physically blended during the processing of commercial PVC materials [15][16][17]. However, the poor compatibility of PVC and additives easily leads to the uneven dispersion of additives and the migration of organic functional components, which results in the decrease in PVC sample efficiency and the increase in the formation of organic by-products during radiolysis [1,18].…”
Section: Introductionmentioning
confidence: 99%